Language use in Brussels and the position of Dutch - Rudi Janssens (Brussels Studies, 2008)
The multilingual character of the population, the number of mixed-language families and the fact that more and more people in Brussels are using services of both traditional language communities is making it increasingly difficult to link a person to a specific language community in Brussels. The linguistic landscape is also becoming more complicated in itself. French definitely remains the lingua franca and the youths who are born in Brussels with an “allochtonous” background are increasingly shifting to the use of French in their new family units. At the same time, however, the number of bilingual families and the number of home languages is rising. The portion of people from Brussels from monolingual Dutch families is slightly dropping and ever more people from Brussels who speak Dutch by birth do this in combination with another language. Nevertheless, these people are increasingly speaking Dutch in public life. English clearly remains in third place in terms of language use and is mainly spoken in a work environment, even though an increasing number of people from Brussels claim they speak.this language better than Dutch. People who live in Brussels find this multilingual environment an important asset, even though political polarisation is always looming around the corner.